The Role of Jigsaw Technique in Promoting Social Awareness and Relationship Skills Among Master’s Students Within the SEL Framework - Aprilia Dyah Kriswinahyu; Regina Putri Nernere; Paulus Kuswandono (STAIN Sultan Abdurrahman Kepulauan Riau, 2025)
Social awareness and relationship skills, integral components of the social-emotional learning (SEL) framework, serve as fundamental objectives in holistic education. However, Indonesia’s SEL concept remains relatively new, particularly in higher education settings. This study examined how learning techniques such as jigsaw enabled the cultivation of social awareness and relationship skills depicted in the SEL framework. Employing a descriptive qualitative research method, this study explored students’ interactions in the jigsaw technique among 19 first-semester Master’s students in the English Education Master Program at Sanata Dharma University. The data were collected through questionnaires, interviews, and observations, which offered a comprehensive understanding of students’ interactions through the jigsaw technique. The findings revealed the potential of jigsaw as a collaborative technique to promote social awareness and relationship skills among higher-education students by exposing students to diverse perspectives and building relationship skills through active communication and collaboration. However, several challenges, such as cultural and emotional barriers and a sense of dominance, inferiority, and trust, emerged in the group interactions that need to be addressed. This study is expected to contribute valuable insights at the higher level of education in Indonesia by applying various learning techniques, one of which is the jigsaw technique, as an effort to implement SEL and improve SEL competencies. The findings provide practical implications for educators and policymakers trying to promote a balance of emotional and social growth alongside students’ academic learning, especially concerning collaborative skills needed in today’s world.